A study on the effectiveness of promotional tools practiced by Mercedes-Benz Malaysia’s merchandising / Muhammad Faizal Samat - Samat, Muhammad Faizal (Faculty of Business and Management, 2011)
Promotion is the communication link between sellers and buyers for the purpose of influencing, informing, or persuading a potential buyer's purchasing decision. Promotional tools contain five elements which are sales promotion, personal selling, advertising, direct marketing, and public relation. A promotional plan can have a wide range of objectives, including: sales increases, new product acceptance, creation of brand equity, positioning, competitive retaliations, or creation of a corporate image. The research title “A Study on The Effectiveness of Promotional Tools Practice by Mercedes- Benz Malaysia’s merchandising” had been conducted to obtain the results at Mercedes-Benz Malaysia (MBM). This research has been answered by 92 respondents through questionnaire. Instead of it, the Statistical Package for the Social Science (SPSS) version 14.0 has been used to summarize the data. Based on this research, the result indicates public relation is the elements that contribute most in promotional tools. Besides that, results shows there are significant relationship between all the elements in the promotional tools which include sales promotion, personal selling, advertising, direct marketing and public relation. As a conclusion, the results of the findings that include the analysis of the demographic profile, general information on promotional tools and elements that most contribute in promotional tools. For the recommendation of this study made based on several logical factors and impact of current situation to the promotional tools practiced.